My sad republic - Gamalinda, Eric 1956- (Bughaw, an imprint of Ateneo De Manila University Press, 2021)
Winner of the Philippine Centennial Literary Award in 1998 and first published in 2000, My Sad Republic is a story of love and loss, obsession and revolution. Set against the epic backdrop of the Spanish-American War and the subsequent war between the United States and the Philippines, it is loosely based on the life of Dionisio Magbuela, also known as Isio, or “The Pope.” One of several leaders of millenarian movements across the archipelago, he rose to legend during a time of immense social and cultural change in the country, where the Spaniards had kept many islands under the spell of sixteenth-century superstition. It was a time that would be pivotal in the history not only of the Philippines, but also the United States, which was on the brink of becoming the next global empire. Blending actual historical sources, folklore, and native ritual, the novel narrates the impact of these upheavals on the lives of several characters whose destinies are altered by a nation about to be born, and its repercussions which linger to this day.